Seismic Attenuation Tomography From 2018 Lombok Earthquakes, Indonesia - Awali Priyono; Andri Dian Nugraha; Andri Dian Nugraha; Muzli Muzli; Muzli Muzli; Ardianto Ardianto; Atin Nur Aulia; Billy Sugiartono Prabowo; Zulfakriza Zulfakriza; Zulfakriza Zulfakriza; Shindy Rosalia; Shindy Rosalia; et al. (Frontiers in Earth Science, 2021)
Local earthquake data was used to determine a three-dimensional (3D) seismic attenuation structure around the aftershock source region of the 2018 Lombok earthquake in Indonesia. The aftershocks were recorded by 13 seismic stations from August 4 to September 9, 2018. The selected data consist of 6,281 P-wave t∗ values from 914 events, which had good t∗ quality in at least four stations. Our results show that the two aftershock clusters northwest and northeast of Lombok Island have different attenuation characteristics. A low P-wave quality factor (low-Qp), low P-wave velocity (Vp), and high ratio of P-wave velocity and S-wave velocity (Vp/Vs), which coincide with a shallower earthquake (<20 km) northwest of Lombok Island, might be associated with a brittle area of basal and imbricated faults influenced by high fluid content. At the same time, the high-Qp, low Vp, and low Vp/Vs, which coincide with a deeper earthquake (>20 km) northeast of Lombok Island, might be associated with an area that lacks fluid content. The difference in fluid content between the northwest and northeast regions might be the cause of the early generation of aftershocks in the northwest area. The significant earthquake that happened on August 5, 2018, took place in a region with moderate Qp, close to the contrast of high and low-Qp and high Vp, which suggests that the earthquake started in a strong material before triggering the shallower aftershocks occurring in an area affected by fluid content. We also identified an old intrusive body on the northeast flank of the Rinjani volcano, which was characterized by a high-Qp, high-velocity, and a high Bouguer anomaly.